Bird‐mediated endozoochory as a potential dispersal mechanism of bony fishes - Lovas‐Kiss, Ádám; Antal, László; Mozsár, Attila; Nyeste, Krisztián; Somogyi, Dóra; Kiss, Balázs; Tóth, Richárd; Tóth, Flórián; Lilla Fazekas, Dorottya; Vitál, Zoltán; Halasi‐Kovács, Béla; Tóth, Pál; et al. (Ecography (Copenhagen), 2024)
The dispersal of fish into distant and isolated habitats remains a topic of continuous discussion in the field of fish biogeography. This is particularly relevant due to the perceived limitation of fish movement to what is known as active dispersal. Fish migration is often confined to interconnected water bodies, underscoring the significance of dispersal for fish inhabiting isolated aquatic habitats. However, empirical evidence for a natural (i.e. not human‐mediated) mechanism has been limited. Here we explore and provide evidence for waterbird‐mediated endozoochory as a possible dispersal mechanism in various fish species and families. We force‐fed mallards Anas plathyrynchos with fertilised eggs of nine bony fish species, covering nine taxonomic families. We recovered viable embryos of five fish taxa in the faeces of mallard, proving the ability of fish eggs to survive the passing of the digestive system of waterbirds. Moreover, the recovered eggs successfully hatched into larvae in two fish species. Taking into the flight speed and numerosity of mallards, as well as the high abundance of fish eggs, our results highlight endozoochory of fish eggs by waterbirds as a possible significant, although likely rare natural dispersal mechanism that can occur across more species than previously known in freshwater fish.